ANALISIS HUBUNGAN STATUS GIZI DAN IKLIM KERJA DENGAN KELELAHAN KERJA DI CATERING HIKMAH FOOD SURABAYA - Ramayanti, Ridha (The Indonesian Journal of Occupational Safety and Health, 2015)
ABSTRACTWork fatigue is condition which some factors have interaction with the workers. Fatigue may occur in the workforce by various factors, such as nutritional status and work climate. This study was conducted to analyze the relationship between nutritional status and work climate with work fatigue in Hikmah Food Catering. This was an observational analytic study using a cross sectional design. Samples size 43 peoples were taken by simple random sampling method. The correlation between the dependent and independent variables were analyzed by spearman correlation test (α = 0,05). Work climate in this catering were kitchen area 29,6°C, non AC 26,5°C area, and air-conditioned area 20,3°C. Spearman correlation test results showed that there was nutritional status which had no significant association with work fatigue (p = 0,954) and there was work climate which had a significant association with work fatigue (p = 0.004). The conclusion of this research is nutritional status has no relation with fatigue, meanwhile work climate have a relation with work fatigue. There are advised for the industry such as providing sufficient drinking water supplies, and installing push pull system ventilation, especially in the kitchen area.Keywords: worker, nutritional status,work climate, work fatigue, catering